New scoring system in assessment of Hoffa’s fat pad synovitis: A comparative study with established scoring systems - Hagiwara, Shigeo (World J Radiol, 2018)
AIM: To investigate the reliability of the established and new scoring methods for Hoffa’s fat pad synovitis using magnetic resonance imaging (MRI). METHODS: A total of 139 knees of 115 patients who underwent MRI of the knee with and without gadolinium contrast were enrolled in this study. Proton density (PD)-weighted, PD-weighted fat-suppressed (PD-FS), and postcontrast T1-weighted fat-suppressed (T1CE) images were used for evaluation. Using contrast and non-contrast images, our grading method for synovitis was performed to measure synovial thickness and signal intensity changes of the fat pad [Synovial membrane (SM) score], which was compared with the established methods, including MRI Osteoarthritis Knee Score (MOAKS), parapatellar synovitis score, Whole-Organ Magnetic Resonance Imaging Score (WORMS), and suprapatellar effusion diameter. Intraclass correlation coefficients (ICC) for intra and interobserver reproducibility and Spearman correlation coefficients (r) were calculated for the parapatellar synovitis score and each scoring method. RESULTS: All of the scores presented substantial to almost perfect intrareliability. Among three readers, effusion diameter had substantial to almost perfect interreliability (ICC = 0.68-0.81) and WORMS had substantial interreliability (ICC = 0.61-0.70). For two out of three readers, there was substantial interreliability for the thickness score in T1CE (ICC = 0.55-0.69), SM scores in T1CE (ICC = 0.56-0.78) and PD-FS (ICC = 0.51-0.79), and parapatellar synovitis score in T1CE (ICC = 0.53-0.72). The parapatellar synovitis score was significantly correlated with the thickness score in T1CE (r = 0.70) and the SM score in T1CE (r = 0.81) and PD-FS (r = 0.65). CONCLUSION: The newly proposed quantitative thickness score on T1CE and the semi-quantitative SM score on T1CE and PD-FS can be useful for Hoffa’s fat pad synovitis.